Design and Analysis of Multi-layer Resistive Ink Film Based Metamaterial Ultra-thin Broadband Absorber - Alsemaid, Osman M.; Babiker, A. Awad; Saad, E. Sulieman (International Journal of Computing and Engineering, 2024)
Purpose: In order to achieve an excellent electromagnetic absorption response for radar applications, this work proposes a design of an ultra-thin, super broadband, high efficiency meta-material that is insensitive to incidence angle. Methodology: a metamaterial based on multilayer resistive ink unit cell is selected, designed and optimized for minimum electromagnetic absorption and widest bandwidth. The equivalent circuit is derived and analyzed and compered using matlab to results from electromagnetic simulator CST. Findings: Calculating approval requires impedance matching in the structure, which makes it challenging to absorb at high frequencies. In this instance, the proposed structure achieves more than 0.98 absorptivity between 4 and 400 GHz, resulting in a broad absorption bandwidth. When exposed to oblique incidences, the proposed structure behaves in the same way for both transverse electric (TE) and transverse magnetic (TM) modes up to 45°. The total thickness of the planned absorber is 2.105 mm, or 0.028 Î»0 at the lowest working frequency. Additionally, find and compare previous radar band reports with the proposed absorber. It is reported to offer more practical feasibility and to be a viable choice for S, C, X, Ku, K, Ka, V, and W bands in addition to millimeter-band radar applications. Unique contribution to theory, practice and policy: Increasing the band width compared to previous studies while increasing the absorption efficiency and reducing the thickness of the metamaterial.